Comparative metabolism of conjugated and unconjugated pterins in Crithidia, Leishmania and African trypanosomes - Ong, Han B.; Wyllie, Susan; Fairlamb, Alan H. (PLOS Neglected Tropical Diseases, 2025)
Author summary Over 75 years have passed since the discovery of “ Crithidia factor” – biopterin – as an essential cofactor involved in several important metabolic functions in mammalian cells. Despite established roles of biopterin as a cofactor in the hydroxylation of aromatic amino acids, the cleavage of glyceryl ether lipids and in the synthesis of nitric oxide in mammalian cells, these metabolic functions either do not exist in kinetoplastids or are unable to account for the essential growth requirements for pterins in these parasites. Here, we have determined structural requirements of pterin analogues that can support growth and survival of three important genera in the order Kinetoplastida. Some quantitative differences are noted in pterin preferences between C. fasciculata and T. brucei, and those of L. major. We find that the sole fate of intracellular pterins in these parasites is reduction to the corresponding tetrahydro intermediate. Folic acid can spare the growth requirement for an unconjugated pterin possibly due to trace amounts being converted to 6-hydroxymethylpterin. Future research directions for elucidation of the essential functions of pterins in these trypanosomatid parasites are discussed.